Master Planning for the Tourist Accommodation in Sala Daeng Nua, Pathumthani - Lappimol, Kritaporn (Fine Arts Journal: Srinakharinwirot University, 2012)
A prominent point of Sala Daeng Nua community is that it reflects the culture and decent lifestyle of Mon people. But the change in economy and society challenges the culture, traditions and ways of life. Therefore, in order to keep the values of the community and society long lasting, a cultural learning and propagating process should be created, directly and indirectly, using cross discipline integration. The Master Planning Project of Tourism Accommodation is a master planning for development of the physical area around Baan Sala Daeng Nua. The project combines culture, tradition and the local architectural style, reflecting the community’s way of life that is pleasant to stay and visit. This project uses the state’s strategy planning for cultural and ecological tourism as a guideline for development. As a result, they will be able to preserve their culture, tradition, lifestyle, and valuable local wisdom in a sustainable way.